Effects of creatine monohydrate timing on resistance training adaptations and body composition after 8 weeks in male and female collegiate athletes - Dinan, Nicholas E.; Hagele, Anthony M.; Jagim, Andrew R.; Miller, Michael G.; Kerksick, Chad M. (Frontiers in Sports and Active Living, 2022)
Background: Limited research is available on the potential impact of creatine monohydrate administration before or after workouts among athletes. This study aimed to investigate the effects of pre- versus post-exercise creatine monohydrate supplementation on resistance training adaptations and body composition. Methods: In a randomized, double-blind, placebo-controlled, parallel design, 34 healthy resistance-trained male and female athletes were randomly assigned and matched according to fat free mass to consume a placebo, or 5-g dose of creatine monohydrate within 1 hour before training, or within 1 hour after training for 8 weeks, while completing a weekly resistance training program. Participants co-ingested 25-gram doses of both whey protein isolate and maltodextrin along with each assigned supplement dose. Body composition, muscular strength, and endurance, along with isometric mid-thigh pull were assessed before and after the 8-week supplementation period. A 3 x 2 mixed factorial (group x time) ANOVA with repeated measures on time were used to evaluate differences. Results: All groups experienced similar and statistically significant increases in fat free mass (+1.34 ± 3.48 kg, p = 0.04), upper (+2.21 ± 5.69 kg, p = 0.04) and lower body strength (+7.32 ± 10.01 kg, p < 0.001), and decreases in body mass (-1.09 ± 2.71 kg, p = 0.03), fat mass (-2.64 ± 4.16 kg, p = 0.001), and percent body fat (-2.85 ± 4.39 kg, p < 0.001). Conclusions: The timing of creatine monohydrate did not exert any additional influence over the measured outcomes.